Comparing Contaminant Removal Costs for Aquifer Recharge with Wastewater with Water Supply Benefits1. (April 2014) - Bloetscher, Frederick; Pleitez, Fernando; Hart, James; Stambaugh, David; Cooper, Jon; Kennedy, Karl; Burack, Lauren Sher
Abstract The use of waters of impaired quality has been suggested as a means to expand available water resources supply for water‐limited communities. An ongoing concern is the safety of supplies that use wastewater because of the potential for introduction of emerging contaminants such as pharmaceuticals into drinking water supplies. Prior research into contaminants of emerging concerns (CECs) have included a variety of methods, but the only consistent removal is with reverse osmosis (RO) membranes, ultraviolet light (UV), and advanced oxidation processes (AOP). However, few of these prior studies have measurable quantities of these contaminants in the influent wastewater, so determining actual removal percentages is difficult. This project was designed to evaluate the removal of CECs to verify that a 3‐log removal of common constituents was realized. Spike testing was used to compare to prior research and to evaluate whether the project costs were competitive with other forms of reuse or other water supplies. The combination of RO/UV/AOP was effective at obtaining a 3‐log removal of CECs, but the RO and UV/AOP processes alone were not capable of removing all substances. However, despite the extensive treatment, the proposed process was both competitive cost‐wise and met the water quality goals.